A novel approach to button battery removal in a two-and-half year-old patient's esophagus after ingestion: a case report - Hung-Chun Wang; Shu-wei Hu; Ke Jian Lin; An-Chyi Chen (BMC, 2022)
Abstract Background Accidental swallowing of a foreign body occurs more frequently in children than in adults. Among these cases, button battery impaction in the esophagus may cause severe complications. While prevention is always ideal, if button battery impaction is suspected, immediate diagnosis and retrieval are important. Case presentation We introduce a novel method for retrieval of a button battery after ingestion by a 2.5-year-old child. When the patient arrived at our center, the battery was incarcerated in the upper esophagus. The battery could not be removed, despite the use of several methods such as alligator forceps under endoscopy and net retrieval. We decided to use a novel method that combined endoscopic balloon extraction and forceps retrieval. This resulted in a push-and-pull effect, creating synergy and easy removal of the battery. There were no long term complications based on the follow-up endoscopy examination. Conclusions This new procedure was very effective for removing the esophageal foreign body. When button battery in esophagus was too tight to be removed by the traditional retrieval methods, this procedure was suggested to use. It could be performed at medical institutions. If it fails or esophageal perforation (iatrogenic or spontaneous) occurs, pediatric surgeons could take over immediately.